Therapy of chronic lymphocytic leukemia (CLL) - from past to present - Anna Gumieniczek; Bogumiła Ciseł; Katarzyna Lipska; Agata A. Filip (Polish Pharmaceutical Society, 2020)
Chronic lymphocytic leukemia (CLL) is the most common form of leukemia in Western European countries. This disease occurs mainly in adult population at an age of over 50 years, more commonly in men. Many years of research have shown that CLL is a disease with a very diverse clinical course and variable sensitivity to treatment. Therefore, in each case of newly diagnosed CLL, the clinical stage, prognostic factors and individualized therapeutic goals should be precisely defined before the treatment initiation. Recent 50 years have been a period of significant development in the treatment of proliferative diseases of the hematopoietic and lymphatic systems. Along with dynamic development of molecular biology techniques, several new specific prognostic markers have been investigated and introduced, allowing better stratification of patients and more accurate direction of the therapy. A lot of effort has gone into searching for the next prognostic factors which allow to determine better probable life span and to implement the successful treatment. Furthermore, many preclinical and clinical studies continually extend the list of effective anticancer drugs, including these for CLL treatment. Increasingly, in addition to standard cytostatics, drugs with more selective mechanisms of action are being tested in monotherapy and new combinations. Considering the historical aspects, only a few anticancer drugs were available 50 years ago. In addition, they mainly presented the one mechanism of action directed at nucleic acids. Today, the list of effective drugs is significantly longer. In addition to typical cytostatics, it also contains drugs with selective mechanisms of action, affecting the cell life processes, their subcellular structures, signaling from outside and inside the cell, surface antigens, as well as drugs that act on the microenvironment of cancer cells and their vascularization. The aim of this paper was to show the historical background in the therapy of leukemia and summarize the current knowledge in CLL biology and treatments. The manuscript is focused on the clinical course of the disease, the main risk factors and mainly, on the available treatment strategies.